The Effect of VCO Processing Method on Blood Glucose, Cholesterol and Pancreatic Profile of Diabetic Mellitus Rats (Sprague Dawley) - Dadang Supriatna; Amilia Dayatri Uray; Made Astawan; Deddy Muchtadi; Tutik Wresdiyati (Balai Besar Industri Agro, 2018)
Virgin Coconut Oil (VCO) can be produced by different methods related to health function. The objective was to study the efficacy of VCO processing method in reducing blood glucose level, cholesterol profile and pancreatic tissue profile of diabetic mellitus (DM) Sprague dawley rats. Four rat groups from five rat groups were injected using alloxan to induce the diabetic condition, while the rest was negative control. VCO-A produced without heat and VCO-B produced with controlled-heat treatment and Coconut Cooking Oil (RBD-CNO) produced with the application of severe heating and chemical (MG) were fed respectively to three rat groups, while the other two rat groups were fed by water and used as negative control (healthy rats) and positive control (DM rats). During 28 days observation, all of the rats blood glucose level were assessed, and at the end of the observation day the rats were terminated to assess the cholesterol and pancreatic tissues profile. VCO-A significantly positive reduced blood glucose level than the others. VCO did not influence DM rats cholesterol profile and all VCO inhibits the rate of pancreatic β cells damage. On 28 days observation all VCO treatments suppressed blood glucose level of DM rats.